Energy Subsidies in Latin America and the Caribbean : Stocktaking and Policy Challenges - Di Bella, Gabriel; Norton, Lawrence; Ntamatungiro, Joseph; Ogawa, Sumiko (Washington, D.C. : International Monetary Fund, 2015)
The oil price decline creates an opportunity to dismantle energy subsidies, which escalated with high oil prices. This paper assesses energy subsidies in Latin America and the Caribbean-about 1.8 percent of GDP in 2011-13 (approximately evenly split between fuel and electricity), and about 3.8 percent of GDP including negative externalities. Countries with poorer institutions subsidize more. Energy-rich countries subsidize fuel more, but low-income countries are more likely to subsidize electricity, as are Central America and the Caribbean. Energy subsidies impose fiscal costs, hurting SOEs, competitiveness, and distribution. The paper overviews country experience with subsidy reform, drawing lessons.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet